Isolation and characterization of caveolae from canine airway and intestinal smooth muscle - Darby, James Peter (My University, 1999)
Calcium (Ca2+ ) for contraction of smooth muscle comes from two sources: release of Ca2+ from an internal site, the sarcoplasmic reticulum (SR), and influx of Ca2+ from the extracellular space across the plasma membrane (PM). We hypothesize that caveolae, flask-shaped invaginations of the PM, are the protected source of Ca2+ . This thesis provides biochemical evidence that supports the hypothesis of caveolae involvement in Ca 2+ handling. Caveolae were isolated from canine tracheal smooth muscle by detergent treatment of PM-derived microsomes. Immunoprecipitation experiments confirmed the presence of calsequestrin and calreticulin in caveolae. Antibodies to caveolin coimmunoprecipitated caveolin with calsequestrin and calreticulin. These experiments also indicated that at least some of the associated calsequestrin and calreticulin are located on the cytoplasmic face of each caveola, since no part of the caveolin protein crosses into the luminal side of each caveola. Immunohistochemistry of fixed tracheal smooth muscle cryosections confirmed that the PM Ca2+ pump, nNOS, and caveolin were all located on the cell periphery, while the SR Ca2+ pump is located deeper in the cell. Based on the results presented here and our previous results of contractility experiments, a model of Ca2+ handling for airway smooth muscle is proposed. This is an extension of the superficial buffer barrier hypothesis first proposed by van Breemen (1986). In our model, caveolae provide the physical basis for the junctional space between the PM and SR. Ca2+ can move into the lumen of the caveolae via the PM Ca2+ pump, and be released from caveolae into the junctional space via L-type Ca 2+ channels. Calsequestrin and calreticulin, located on the cytoplasmic face of caveolae, may act as a physical barrier facilitating the direct refilling of the closely associated SR with Ca2+ . Similarly, nitric oxide, produced by the nNOS located on the caveolae, may inhibit release of Ca 2+ by the SR, thereby enhancing refilling. The Ca2+ in the lumen of the caveolae may be retained by calsequestrin, calreticulin, or another unidentified Ca2+ binding protein located in the caveolae lumen. (Abstract shortened by UMI.)
Keywords: Medical Sciences; Medical Sciences